Habitus Jurnalistik dan Konstruksi Kebenaran: Studi Kritis Kontradiksi Framing Berita Perang pada Republika dan Detik.Com - Muhammad Fahmi (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2026)
This research aims to dissect how mass media constructs the reality of war through the mechanisms of issue selection and the highlighting of specific aspects. Utilizing Robert Entman's framing model, this study explores four key elements within news texts: defining problems, diagnosing causes, making moral judgments, and providing treatment recommendations. The analytical focus is directed toward the differing framing directions between national media outlets that hold distinct ideological tendencies in portraying the actors involved in the conflict. The findings indicate that media outlets do not merely report facts on the ground; rather, they are actively engaged in the "politics of labeling," which influences public perception regarding the legitimacy of violence and humanity. The results of this study contribute to the field of the sociology of communication, specifically concerning the role of media as an agent of social construction within global conflict discourse in the era of surveillance capitalism.